Anopheles prachongae, a new species of the Gigas Complex of subgenus Anopheles (Diptera: Culicidae) in Thailand, contrasted with known forms of the complex - Harbach, Ralph E.; Rattanarithikul, Rampa; Harrison, Bruce A. (Zootaxa, 2017)
Anopheles (Anopheles) prachongae, a new species of the Gigas Complex from northern Thailand, is described and illustrated in the adult, pupal and larval stages, and bionomics and chaetotaxy tables are provided for the immature stages. The species is distinguished from Anopheles baileyi, the only other species of the complex known to occur in Thailand, and contrasted with other taxa of the complex that occur in the Oriental Region. Available morphological data indicate that An. gigas sumatrana is unique and is therefore formally afforded species status. The three other Sumatran subspecies may be conspecific. The taxonomic status of the non-Sumatran subspecies, i.e. crockeri (Borneo), formosus (Philippines), refutans (Sri Lanka) and simlensis (south-central Asia), is questioned but their status is unchanged pending further study.